Network constrained economic dispatch of integrated heat and electricity systems through mixed integer conic programming - Huang, Shaojun; Tang, Weichu; Wu, Qiuwei; Li, Canbing (Energy (Oxford), 2019)
This paper proposes an economic dispatch method for an integrated heat and electricity system with respect to network constraints. Network constraints are usually nonlinear and can cause severe difficulties for optimization solvers. Particularly, in a heating network, the mass flow mixing at each node and the pressure and temperature drop along each pipe involve both hydraulic and thermal processes, which can cause high nonlinearity that has not been properly modeled. This paper will firstly model the power and heat network constraints by using a nonlinear model, which is accurate but hard to solve. Then, simplification and convexification will be employed to reform the nonlinear constraints to linear and conic ones. Consequently, the entire economic dispatch problem will be modeled as a mixed integer conic programming problem. Because the proposed model allows for the changes of the mass flow rate and direction, an optimal mass flow profile can be achieved along with the solution of the economic dispatch. Case studies on an integrated district heating and power system with a portfolio of power and heat sources show that the proposed economic dispatch model can handle the complexity of the network constraints and make optimal dispatch plans for multi-energy systems. •An economic dispatch method based on mixed integer conic programming.•A multi-energy system with a portfolio of power and heat sources is modeled.•Varying mass flow rates and directions of district heating systems are modeled.•The model is efficient on both the computation time and the cost saving.•An optimal mass flow profile is shown along with the optimal dispatch results.